A review on physiochemical treatment of sulfolane in aqueous media. Issue 4 (August 2021) - Yu, Linlong; Khan, Muhammad Faizan; Achari, Gopal
Abstract: Sulfolane is an organic solvent that is primarily used in petrochemical industries to remove acid compounds from sour natural gas. In recent years, sulfolane has been reported to contaminate ground and surface waters around many gas processing plant sites in North America. It is highly soluble in water and has poor adsorption on soil, which makes it easy for offsite migration in the subsurface. Numerous methods have been developed and applied in treating sulfolane contaminated waters. In early years, the degradation of sulfolane had focused on biological processes, which utilized microbial metabolism under aerobic conditions. However, biological processes require relatively longer treatment times (>10 h) and are highly dependent on environmental factors such as temperature, dissolved oxygen and presence of nutrients. Recently, to overcome these limitations, abiotic technologies including advanced oxidation processes and activated carbon adsorption have been developed to treat sulfolane impacted water. Both abiotic technologies can degrade or remove sulfolane from water much faster than biological processes. In this review paper, the advances on treating sulfolane impacted water using advanced oxidation processes and activated carbon adsorption is presented. The advanced oxidation processes that have been reported in literature and reviewed here for treating sulfolane include ultraviolet-C (UVC)/H2 O2, UVC/O3, UVC/persulfate, TiO2 photocatalysis, Fenton reaction, catalytic ozonation, wet oxidation and others. Graphical Abstract: ga1 Highlights: Physiochemical treatment of sulfolane in water was systematically reviewed. Pilot AOPs and activated carbon systems are effective in treating sulfolane. A possible sulfolane degradation pathway by hydroxyl radical is proposed. Water chemistry impacts the performance of different technologies.